Recent Advances in Sn‐Based Heterojunction‐Type Anode Materials for Alkali‐Ion Batteries - Hui Li; Zhiqiang Liu; Lei Li; Yehong Zhang; Zeheng Li; Huixin Lan; Zhenhe Zhu; Yuchen Wu; Jiajia Li; Chuanbo Zheng; Jun Lu (Carbon Energy)
ABSTRACT The urgent demand for clean energy solutions has intensified the search for advanced storage materials, with rechargeable alkali‐ion batteries (AIBs) playing a pivotal role in electrochemical energy storage. Enhancing electrode performance is critical to addressing the increasing need for high‐energy and high‐power AIBs. Next‐generation anode materials face significant challenges, including limited energy storage capacities and complex reaction mechanisms that complicate structural modeling. Sn‐based materials have emerged as promising candidates for AIBs due to their inherent advantages. Recent research has increasingly focused on the development of heterojunctions as a strategy to enhance the performance of Sn‐based anode materials. Despite significant advances in this field, comprehensive reviews summarizing the latest developments are still sparse. This review provides a detailed overview of recent progress in Sn‐based heterojunction‐type anode materials. It begins with an explanation of the concept of heterojunctions, including their fabrication, characterization, and classification. Cutting‐edge research on Sn‐based heterojunction‐type anodes for AIBs is highlighted. Finally, the review summarizes the latest advancements in heterojunction technology and discusses future directions for research and development in this area.